The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.14740/jnr362w
|View full text |Cite
|
Sign up to set email alerts
|

The Role of D-Dimer, Fibrinogen and C-Reactive Protein as Plasma Biomarkers in Acute Ischemic Stroke

Abstract: Background: Previous studies on pathophysiology suggest a role of inflammation in atherothrombotic stroke and intracardiac thrombosis in cardioembolic stroke. We explored the magnitude of D-dimer, fibrinogen and C-reactive protein (CRP) as biomarkers in acute ischemic cerebral stroke and their relation to ischemic stroke subtypes and their impact on stroke outcome after 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
5
6
0
Order By: Relevance
“…As regards CRP as a biomarker for diagnosis of CES, we found that CRP level was higher in non-CES patients but without any significant difference between CES and non-CES patients ( Table 1). This is in agreement with Alvarez-Perez and colleagues [25] and Melake and colleagues [26]. They found that CRP levels were higher among the atherosclerotic group compared with those of CES, and this difference possesed a highly statistical significant effect, and contributed these results to the higher degree of inflammation in atherosclerotic stroke subtype.…”
Section: Discussionsupporting
confidence: 89%
“…As regards CRP as a biomarker for diagnosis of CES, we found that CRP level was higher in non-CES patients but without any significant difference between CES and non-CES patients ( Table 1). This is in agreement with Alvarez-Perez and colleagues [25] and Melake and colleagues [26]. They found that CRP levels were higher among the atherosclerotic group compared with those of CES, and this difference possesed a highly statistical significant effect, and contributed these results to the higher degree of inflammation in atherosclerotic stroke subtype.…”
Section: Discussionsupporting
confidence: 89%
“…Suppression of the inflammatory mediators have been shown to limit injury [10]. Increased inflammatory biomark-ers (D-dimer, C-Reactive Protein and Fibrinogen) have been shown to increase stroke severity and disability within 30 days [11], while erythrocyte sedimentation rate has not been shown to predict the outcome of stroke [12]. Chest imaging of COVID-19 patients show consolidation, ground glass opacities and bilateral lung involvement, which were consistent with findings in our patient [1,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…These levels are directly proportional to the clinical outcome and mortality. Procalcitonin levels are normal unless there is a concomitant bacterial infection [1,6,7,11].…”
Section: Discussionmentioning
confidence: 99%
“…Another study published in the same year evaluated the role of DD, FIB, and CRP as plasma biomarkers in acute ischemic stroke. It proved that these biomarkers might be helpful in detecting the etiology of acute cerebral vascular stroke [16]. A study released in 2016 evaluated CRP, FIB, and DD in patients with progressive cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%